Pediatric Obesity Algorithm: A Practical Approach to Obesity Diagnosis and Management - Cuda, Suzanne E.; Censani, Marisa (Frontiers in Pediatrics, 2019)
Childhood obesity is a growing global health problem. Despite a continual rise in the rate of childhood obesity in the United States and other developed countries over the last 30 years, there is still no clear treatment strategy. Practitioners often do not know where to turn to find guidance on managing the nearly one third of their population who present for medical care either with obesity that coexists with other medical problems or because of obesity. The Pediatric Obesity Algorithm is an evidence based roadmap for the diagnosis and management of children with obesity. In this article, we present the case of the management of an adolescent male with severe obesity and summarize a variety of topics from the Pediatric Obesity Algorithm pertaining to pediatric obesity diagnosis, evaluation, and management including epigenetics, assessment, differential diagnosis, review of systems and diagnostic work up, physical exam, age specific management, comorbidities, use of medications and surgery, and medication associated weight gain. Identifying and treating these children as early as possible is important, as is identifying comorbid conditions. Earlier and more comprehensive management through resources such as the Pediatric Obesity Algorithm serve to help guide health care practitioners with a practical and evidence based approach to the diagnosis and management of children with obesity, and provide families with the tools needed for a healthy future